Umthonyama - Lallie, Lungile (Little Theatre, 2024)
Umthonyama explores the politics of black queer visibility and contested belonging within the evolving culture of amaXhosa people. Black queer performance practitioners, are practically and theoretically foregrounded in this thesis to demonstrate the sophisticated ways in which we become visible, create space, and locate ourselves within the culture. Black queer erasure is furthermore complicated by examining how Xhosa contemporary popular culture and music is influenced by Xhosa religious practice, which then becomes a fertile site for both the subversion and reimagining of new cultural identities and belonging. I draw chiefly on José Esteban Muñoz's concept of 'disidentification' and Viktor Shklyovsky's concept of 'defamiliarization' as theoretical and formal approaches in my enquiry. To these ends, my thesis production, Umthonyama --cyclical, durational live-art installation, work -- is stylized as a queer 'homily' that rehearses and celebrates a queer genealogy of black Xhosa identity felt and contested at the level of the intimate body. Citing the aesthetics and politics of black artists such as Athi-Patra Ruga, Thandiswa Mazwai, Camagwini, and Ntombethongo, the installation acts as the central site of experience, encounter, collision, for reframing neocolonial codes of spiritual, traditional, and popular modes of emerging Xhosa culture